Development of a calculation tool for the performance evaluation of lightweight steel framed (LSF) walls - Ribeiro, Telmo Miguel Martins (2022)
Dissertação de Mestrado em Eficiência Acústica e Energética para uma Construção Sustentável apresentada à Faculdade de Ciências e Tecnologia